William Penn: a life - Murphy, Andrew R. (Oxford University Press, Incorporated, 2018)
It may surprise many that William Penn, who founded one of the thirteen original American colonies, spent just four years on American soil. Even more surprising, though, is Penn's remarkable impact on the fundamental principles of religious freedom on both sides of the Atlantic, especially given his tumultuous life: from his youthful radicalism as leader of the Quaker movement to his role as governor and proprietor of a major American colony; from royal courtier to alleged traitor to the Crown. In the first major biography of this important transatlantic figure in more than forty years, Andrew R. Murphy takes readers through the defiant and complex life of a religious dissenter, political theorist, and social activist